Etika Verifikasi Informasi (Tabayyun) di Era Digital: Studi Tematik Al-Qur'an tentang Pemberantasan Hoaks dan Fitnah - Maya Astria; Darliyati Lubis; Sirrul Aulia; Ali Imran (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The digital era has brought humanity into a post-truth phase, where emotional perceptions often trump objective facts, thus triggering the widespread spread of hoaxes and slander that undermine social cohesion. This study aims to reformulate the ethics of information verification through the concept of Tabayyun in the Qur'an as a theological and practical solution in the era of information disruption. Using a qualitative research method based on library research and a Thematic Tafsir (Maudhu'i) approach, this study collects and analyzes verses related to information validation, verbal honesty, and the social impact of disinformation. The results show that tabayyun is not merely a technical fact-checking procedure, but rather an epistemic and spiritual obligation rooted in piety. This study identifies that the concept of